Problemática psicosocial en comunidades residentes en la zona de amenaza volcánica alta del volcán Galeras: una perspectiva para el acompañamiento psicosocial desde la psicología comunitaria - Ojeda Rosero, Dayra Elizabeth (Universidad y Salud, 2008)
The Psychosocial Studies research group (Department of Community Psychology) at the University of Nariño, conducted a qualitative research, with ethnography elements and approaches which enabled recognize perceptions of psychosocial problems in communities living in High Risk of volcano zone (Colombia-Nariño). Through this study succeeded in identifying and bringing together the psychosocial problems in different analytical categories: perception of risk, emocional demonstrations, cognitive-behavioral, relationship-community and institutions, communal conflicts and problems in shelters. There is a reflection from the Community Psychology, taking into account the characteristics of the situation of ZAVA, which allows a particular perspective to the professional and scientific analysis of the subject. Taking into account the problems, and considering the legal, institutional and community dynamics are proposed elements for the boarding process of psychosocial support, academically based, in consultation with the communities of the ZAVA and institutions involved with the to generate scenarios conducive to the well-being in communities. This proposal incorporates fundamentals of Psychosocial Stress Model and Model Sociocommunity, including relevant aspects derived from the concepts about, Community Resilience and Mental Health.